Comparative Plasma Endocrine, Metabolic and Mineral Profile of Cyclic, Acyclic, Endometritic and Pregnant Buffaloes - Patel, Binal R; Panchal, MT; Dhami, AJ; Sarvaiya, NP; Pathan, MM (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Circulating concentrations of hormones, metabolites, and minerals reflect the physio-pathological status of reproduction in animals. Thisstudy was carried out on infertile (anestrus, endometritic), normal healthy cyclic and pregnant buffaloes to evaluate the comparativeplasma progesterone (P4) and estrogen (E2) hormones, plasma total protein, total cholesterol, calcium, and phosphorus profile. Thestudy showed higher mean plasma E2 and lower P4 levels in the follicular phase of estrous cycle in buffaloes. Significantly (p
Keywords: Acyclic; Buffalo; Cyclic; Endometritis and Pregnancy; Endocrine metabolic; minerals profile